Experiences of Female Informal Traders in Namibia during the National Coronavirus Lockdown of 2020 - Matomola, Lisa Namasiku (Graduate School of Business (GSB), 2024)
Background. In emerging economies, the informal sector is often the largest sector of the economy. Namibia is no exception, with approximately 58% of the Namibian population deriving a livelihood within the informal sector of the economy (Namibia Statistics Agency, 2018). According to the Namibia Statistics Agency (2018), most informal traders are women (61.2%) who mostly hold junior secondary education levels (41.1%). Women often find it harder to get jobs in the formal sector than their male counterparts, and when they do, they are often paid lower salaries resulting in a gender pay gap (Mwaba, 2010). As a result, many women turn to informal employment to provide for themselves and their families, and informal traders are mostly women (61.2%; The Informal Sector Survey, 2001). In many African nations, women are often undermined by their male counterparts, who use traditional conservative norms to subjugate them. The same principles are often also observed among women working in the informal sector (Mwaba, 2010). Despite women making up the largest proportion of informal traders, as suggested above, there is still little being done to address the challenges and experiences of women informal traders, and it is hoped that this study will contribute to alleviating the plight of this group. The situation informal traders find themselves in was severely impacted when a nationwide lockdown was declared, which was implemented to slow down the spread of COVID-19. Aim of the study. The aim of the present research study was to gain a better understanding of the experiences of female informal traders during the COVID-19 lockdown in Namibia. It was hoped that collecting information from female informal traders would contribute to closing a gap in the literature, as well as generate insights that could inform policymakers and those in government to adopt measures to better protect, support and develop this vulnerable group of people who provide an important service and positively contribute to the lives of many people. xii Procedure and Materials. An exploratory research design was utilised for the purposes of the current research study, and primary qualitative data were collected using in-depth interviews. The approach to conducting the research study can further be described as having been cross-sectional and of the ex post facto variety. Materials A semi-structured interview guide was developed and consisted of both open-ended and closed-ended questions. The questions were designed to collect information from participants related to their demographic information, as well as their experiences as informal traders before and during the COVID-19 lockdown in Namibia. Sampling and Realised Sample. Judgement or purposive sampling was used to obtain a non-probable sample of n=20 female informal traders operating within Windhoek, the capital city of Namibia. Participants were selected using several inclusion criteria to ensure they were suitable for the purposes of the research study. Findings. The women who participated in the research study reported that the national lockdown severely affected their businesses as they were not permitted to trade for at least two months. Moreover, since their clients' movements were also restricted, a sharp decline in sales during this period was experienced. Not being able to generate an income meant that many informal traders depleted the little savings they had to buy food and survive over the period. The situation this group of female informal traders found themselves in was not unfamiliar to them; however, the impact of the lockdown greatly exacerbated the situation they have found themselves in for many years now. As a result, when the lockdown restrictions were lifted, about half of the women who participated in the research study reported having to take loans out to buy stock for their businesses to start trading again. Securing loans, however, has always proven challenging for them because they classified as a risky group when it comes to repayment as they have no assets.